ANALISIS KEMAMPUAN MENARIK KESIMPULAN DAN MENERAPKAN KONSEP - Herni Agustiani; Ila Rosilawati; Tasviri Efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2013)
This research aimed to describe the ability of drawing conclusions and applying concepts on the acid-base matery through the application of LC3E for students groups of high, intermediate and low level group. The subjects in this research were students of Grade XI Science 4 Senior High School 12 Bandar Lampung Academic Year 2012/2013.  This research was a descriptive research, used the pre-experimental method  with a one-shot case study design.  Data analysis used descriptive analysis. Based on the result of data analysis summarized that ability of drawing conclusions in high level group: almost half were excellent and the others were good. In  intermediate level group, almost all were good and the others were excellent. In low level group, small part were good enough and the others were good. The ability of applying the concept in high level group: almost all were excellent and the others were good. In  intermediate level group, just small part were excellent, just small part were good enough and the others were good. In low level group, almost half were excellent, almost half were good and the other were good enough.Kata Kunci: learning cycle 3E, kemampuan menarik kesimpulan, menerapkan konsep, kelompok kognitif.